Gloria Estefan singer and entertainer - Gonzales, Doreen (Springfield, NJ Enslow Publishers, 1998)
Presents a biography of the Cuban-born singer and composer who has recorded such hits as "Into the Light," "Conga," and "Reach."
Includes bibliographical references and index.
Grade level : 4 - 6
Keywords: Estefan, Gloria -- Juvenile literature; Singers -- Biography -- Juvenile literature. -- United States; Singers; Cuban Americans -- Biography; Women -- Biography